Answer :
Answer:
The fourth option is correct K2 = (1/K1)2
Explanation:
Step 1: Data given
(1) NO(g) + ½O2(g) ⇆ NO2(g)
(2) 2NO2(g) ⇆ 2NO(g) + O2(g)
Step 2: Calculate K1
K1 = [NO2] / [NO][O2]^0.5
Step 3: Calculate K2
K2 = [NO]²[O2]/[NO2]²
Step 4: When we square the first equation
K1² = [NO2]² / [NO]²[O2]
Step 5: Calculate the reverse reaction
1/K1² = [NO]²[O2] / [NO2]² = K2
So K2 = 1/K1² = 1²/K1²
The fourth option is correct K2 = (1/K1)2
Answer:
The answer is K2 = (1/K1)2
Explanation:
For the first reaction:
NO + 1/2O₂ = NO₂
[tex]K_{1} =\frac{[NO_{2}] }{[NO][O_{2}]^{1/2} }[/tex]
For the second reaction:
2NO₂ = 2NO + O₂
[tex]K_{2} =\frac{[NO]^{2}[O_{2}] }{[NO_{2}]^{2} }=\frac{[NO][O_{2}]^{1/2} }{[NO_{2}]^{2} } =(\frac{1}{K_{1} } )^{2}[/tex]